Implementation of the Notary Position Professional Code of Ethics in Cooperation with Banks - Ridwan, Ahmad; Sakinah, Nailus; Anwar, Syahrul; Kania, Dede (Yayasan Mentari Madani, 2024)
The purpose of this research is to find out the implementation of the code of ethics of the notary profession in cooperation with the Bank. The notary profession has the main task of making authentic deeds that serve as written evidence to resolve legal disputes in the future. This is relevant to maintaining the integrity, fairness, and compliance of notaries with the code of ethics in cooperation with banks. The researcher used a qualitative method. The data collection techniques are sourced from journals, books, the internet. The results of his research state that cooperation between notaries and banks continues to occur or maybe notaries become bank subscriptions, several aspects need to be considered. The concept of independence remains valid as long as there is no written provision that regulates otherwise in the cooperation agreement. The independence of a Notary in carrying out his duties lies in the function of notarization or recording in writing and authentically in accordance with the wishes of the confronters. Notaries are not dependent on any party and may not be directed by any party, and must remain neutral towards the parties.